(untitled) (Journal of Forestry, 2024)
During field research conducted from 2022 to 2023 on the island of Koločep, near the city of Dubrovnik, the spontaneous emergence of the non-native species Diospyros virginiana L. (common persimmon) was observed outside its primary cultivation area. This ornamental plant is part of the park dendroflora. D. virginiana began appearing spontaneously on the eastern side of the road between the two main settlements of the island, Gornje Čelo and Donje Čelo. It has established itself in an agricultural habitat within an abandoned olive grove covering an area of about 2900 m2. The plot, no longer under cultivation, is predominantly covered with ruderal and weedy vegetation, featuring an herbaceous ground layer identified as Dauco majori-Foeniculetum vulgaris. In this area, D. virginiana attains an average height of 1 to 2 meters, enveloping and suppressing the remaining Olea europaea L. trees. The plant spreads vegetatively and possesses a robust root system extending laterally for several meters, completely covering the area. Additionally, it has grown into a dry stone wall structure along the road. According to the author’s proposal, it was recently entered in the FCD as 2.1.1.3, a potentially invasive species, to provide a basis for future monitoring. Considering its invasive potential and the environmental damage it may cause, the authors suggest the eradication of the species from the area before it spreads to surrounding regions.